Studi Perencanaan Kabel Bawah Tanah di Proyek Perumahan Anvaya Townhouse Kota Bogor - Bayu Satriyo Utomo; Sapto Nisworo; Deria Pravitasari (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The electricity distribution system is distributed in two ways, namely aerial distribution channels and underground distribution channels. The choice to use underground distribution network cables is one alternative for security, and provides aesthetic value to buildings or cities that use underground cable channel distribution. In this plan, medium voltage and low voltage are planned by determining the type of cable in this study using NYFGbY and NYRGbY cables with protective steel cheeks, and steel wire. The construction of the cable installation is in accordance with the standard ground cable construction and is assisted by a layout drawn with Autocad software, this planning also calculates the voltage shrinkage with two methods, namely the manual method with the maximum voltage on the Main Distribution Panel (MDP) panel to the Sub Distribution Panel (SDP) based on the calculation obtained a value of 2.029 V with a percentage of 0.5% the calculation has met the SPLN No 72 Year 1987 Standard from the results of manual calculations not reaching 4%, then with the simulation method with ETAP 19 software. 0.1 maximum voltage on the Main Distribution Panel (MDP) panel to the Sub Distribution Panel (SDP) obtained voltage shrinkage at MDP to SDP, namely 1.75% of simulation results meet SPLN Standard No. 72 of 1987 from the results of manual calculations not reaching 4%.